Fertilizers and Pesticides Consumption at the Global and the EU level and in Romania - Agatha POPESCU; Valentin SERBAN (Communications of International Proceedings, 2021)
The paper analyzed the consumption of fertilizers and pesticides in the world, the EU and Romania, based on the data collected from various official statistical information sources. The classifications and comparisons were made to establish the big and small consumers, the position of the EU countries and especially Romania regarding fertilizer and pesticides consumption. The global average consumption of mineral fertilizers reached 199.6 kg/ha, but the highest level exceeded 3,500 kg/ha, a real "alarm bell" regarding the risk for environment pollution and food safety. Also, 24.9 kg/ha pesticides represents the world highest mean consumption. In the EU, both fertilizer and pesticides consumption is much smaller than the global mean, ranging between a little bit more than 100 kg/ha in four member states  and below 60kg/ha in three member states. The top consumption of pesticides is 12 kg/ha, twice less than the global highest level, while the lowest level accounts for 0.6 kg/ha. In 2020, Romania  consumed in average 98 kg/ha mineral fertilizer active substance, of which nitrogen 59.2 kg/ha and 0.8 kg/ha pesticides, which are among the lowest levels in the EU, which justify its low risk for pesticides indicator accounting for 48. The results emphasized the efforts made in the EU countries to reduce the use of mineral fertilizers and pesticides and to pass to bio alternatives  for developing a sustainable agriculture according to Green Deal 2021 which has to reduce health and environment risk and ensure food safety.
Keywords: Fertilizers; Pesticides; Consumption; Worldwide; EU; Romania.